Anaerobic caproate production on carbon chain elongation: Effect of lactate/butyrate ratio, concentration and operation mode. (June 2021) - Xie, Shanbiao; Ma, Jingwei; Li, Lu; He, Qiulai; Xu, Peng; Ke, Shuizhou; Shi, Zhou
Highlights: Lactate/butyrate ratio and concentration had significant impact on MCFA production. Low pH and low substrates concentration effectively inhibited acrylate pathway. High butyrate concentration suppressed odd-carbon-number carboxylates production. Semi-continuous operation mode enhanced caproate production by about 3 times. Abstract: The objective of this study was to understand how lactate-to-butyrate ratio and substrates concentrations affect the caproate production and product structure. The results showed that a higher butyrate-to-lactate ratio is beneficial to caproate production at low initial lactate concentration. Low pH (5.0) and low substrate concentration (20 mM and 40 mM) effectively decreased propionate production via restrained acrylate pathway, resulting in higher electron efficiency of caproate. With the optimum mole ratio of lactate to butyrate (1:4) and 80 mM initial butyrate concentration, the electron efficiency of caproate reached the maximum (43.10%). Moreover, high butyrate concentration suppressed the production of odd-carbon-number carboxylates while promoting the production of caproate. Compared with the batch operation, the caproate production in semi-continuous operation was enhanced by 3.45 times to 30.91 ± 1.07 mM as the acrylate pathway was successfully inhibited in semi-continuous experiments due to low pH and low lactate concentration.